(untitled) (Asian-Australasian Journal of Bioscience and Biotechnology, 2018)
The study was conducted at the experimental field of the Bangladesh Agricultural University (BAU) to demonstrate the evidence of the suitability of dairy farm’s wastewater on soil properties in a maize field under three fertilizer doses and three irrigation treatments. Irrigation had three treatments - I1: Irrigation with fresh water, I2: Irrigation with mixed water (fresh water: dairy farm’s wastewater = 1:1) and I3: Irrigation with raw wastewater. There were three fertilizer treatments - F0: No fertilizer, F1: Half of recommended dose fertilizer and F2: Full dose fertilizer. Wastewater contained different nutrients and organic matter, which optimistically contributed to the soil in the maize field. Both irrigation and fertilizer treatments employed different degrees of influence on the soil health. For the effect of irrigation treatments, the highest values of EC (0.223 dS/m), pH (8.18), OC (0.3733 %), total N (0.046 %), P (7.65 ppm), K (33 .08 ppm), Ca (297.80 ppm) and Mg (109.9 ppm) were recorded under the treatment of I3, I1, I1, I1, I3, I1, I2 and I3, respectively, and the lowest values of the soil quality parameters were counted under the treatment of I1, I3, I3, I3, I2, I2, I1, and I2, respectively. In case of fertilizer treatments, the maximum values of the soil quality parameters were obtained under the treatment of F2, F2, F0, F1, F2, F1, F1, and F1, respectively, and the lowest values were obtained under the treatment of F0, F0, F1, F0, F0, F0, F0, F2, respectively. For the irrigation and fertilizer interactions, the maximum values of EC (0.250 dS/m), pH (8.20), OC (0.38 %), total N (0.059 %), P (8.37 ppm), K (48.0 ppm), Ca (374.9 ppm) and Mg (112.60 ppm) were recorded under the treatment combinations I3F0, I1F2, I3F2, I1F2, I3F2, I3F1, I2F0 and I3F2, respectively, and thye lowest values were recorded under the treatment combinations of I2F0, I1F0, I1F0, I1F0, I2F0, I2F0, I2F2 and I2F2, respectively. Both the irrigation and fertilizer treatments and their combinations did not cause any significant variation in the quality parameters of the soil, except soil pH and phosphorus (P) content of the soil in the maize field. Asian Australas. J. Biosci. Biotechnol. 2018, 3 (1), 33-39